A national survey of Chinese medicine doctors and clinical practice guidelines in China - Mengyu Liu; Chi Zhang; Qinglin Zha; Wei Yang; Ya Yuwen; Linda Zhong; Zhaoxiang Bian; Xuejie Han; Aiping Lu (BMC, 2017)
Abstract Background Clinical practice guidelines (CPGs) for Chinese medicine (CM) are being developed to assist doctors with appropriate decisions concerning CM care. To date, there has been little investigation on the perspectives of those to whom the guidelines are directed. Methods A self-administered questionnaire was sent to 4503 doctors in 28 provinces of China in the latter half of 2012. Questions were organized around the topics of knowledge, application, practice changes, beliefs and outcomes of implementation. Basic classificatory data on specialties and years of qualification were also collected. Results Replies were received from 4495 CM doctors (99.82%). Of these, 85.56% of CM doctors reported being familiar with CPG recommendations, but the overall adherence rate was only 50.39%. The length of time practicing CM may influence the rate of adherence, since 709 doctors (51.90%) with less than 5 years of experience reported never having followed CPGs. Doctors in nine specialties showed a modest degree of homogeneity in their attitudes towards CM diagnosis and treatment, which were generally positive. Most doctors regarded CPG-recommended therapies as safe (92%), economic (84%), and effective (76%). Approximately four-fifths of those questioned selected 'acceptable' (60.84%) and 'acceptable after revision' (19.23%) regarding their comprehensive assessment of the CPGs. Conclusions An encouraging result from this survey is that the majority of CM doctors support the concept of CPGs for the practice of CM. However, the results of this survey also suggest that improving the adherence of CM doctors to the guidelines remains a major challenge to improving the practice standards for CM.